The negative effects of temperature increase on bacterial respiration are independent of changes in community composition. Issue 2 (23rd January 2014) - Pires, Aliny P. F.; Guariento, Rafael D.; Laque, Thais; Esteves, Francisco A.; Farjalla, Vinicius F.
Summary Temporal changes in environmental conditions and in bacterial community composition (BCC) regulate bacterial processes and ecosystem services. An increase in temperature accelerates bacterial processes in polar or temperate regions, but this relationship has not been documented for the tropics. Here, we tested the interactive effects of changing the BCC and increasing the water temperature on tropical bacterial respiration (BR). The BCC was manipulated through successional changes of the bacterial community in a filtered water sample from a tropical coastal lagoon. Four succession incubation periods (120, 240, 288 and 336 h) and four different water temperatures (23, 28, 33 and 38oC) were tested in a full‐factorial design microcosm experiment. Both the BCC and the temperature had significant individual, but not interactive, effects on BR. Temperature increasing consistently decreased BR, while there was no clear pattern of successional effects on BR observed. No BCC tested was able to diminish the negative effects of temperature increases on BR. Our results suggest that the effects of an increasing temperature can negatively affect BR, even in tropical ecosystems with different BCC.